Multiple Exclusion Statistics - Riccardo, Julián José (2019)
A new distribution for systems of particles obeying statistical exclusion of co-rrelated states is presented following Haldane's state counting. It relies upon aconjecture to deal with the multiple exclusion that takes place when the states avai-lable to single particles are spatially correlated and it can be simultaneously excludedby more than one particle. Haldane's statistics and Wu's distribution are recoveredin the limit of non-correlated states (constant statistical exclusion) of the multipleexclusion statistics. In addition, the exclusion spectrum function G(n) is introducedto account for the dependence of the statistical exclusion on the occupation-numbern. Results of thermodynamics and state occupation are shown for ideal lattice gases oflinear particles of size k (k-mers) where multiple exclusion occurs. Remarkable agree-ment is found with simulations from k=2 to 10 where multiple exclusion dominates as k increases.